(untitled) (European Journal of Pure and Applied Mathematics, 2025)
This article introduces an algorithm designed to approximate a common fixed point for a class of graph-based mappings in a real Hilbert space. We show that the sequence generated by this algorithm weakly converges to a common fixed point. Moreover, we explore the algorithm’s practical application by investigating its effectiveness in solving image recovery problems related to PM2.5. Its performance is then evaluated by comparing it to existing methods.